Perceived values of the hotel website quality and behavioral loyalty among baby boomers/ Nur Syahira Bibit and Muhammad Izzat Zulkifly - Bibit, Nur Syahira; Zulkifly, Muhammad Izzat (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This research focuses on three dimensions of the hotel website's perceived values towards behavioral loyalty among baby boomers due to a common perception that they are eager to embrace new technologies. The baby boomers are considered one of the industry's most competitive business segments. This research aims to empirically examine the impact of the hotel website content on the behavioral loyalty of customers among baby boomers. The study adopted a quantitative approach and the samples comprised hotel online user among baby boomers in Selangor one of the states in Malaysia. Using the snowbal strategy, 388 data from the respondents from the baby boomer's generation in Malaysia were collected. The study found a positive relationship between perceived values of the hotel website and behavioral loyalty among baby boomers. This research provides new information to the hotel industry on improving the level of customer's behavioral loyalty, especially among the baby boomer's generation. Hopefully, the finding in this study will help the service organization modify their strategy to increase the number of hotel website users.